Doxorubicin-Loaded Tumor-Targeting Peptide-Decorated Polypeptide Nanoparticles for Treating Primary Orthotopic Colon Cancer - Liu, Guoliang; Wang, Min; He, Hongyu; Li, Jiannan (Frontiers in Pharmacology, 2021)
Colorectal cancer is the third most common malignant disease worldwide, and chemotherapy has been highlighted for the treatment of colorectal cancer. However, the therapeutic effects of chemotherapy are unsatisfactory for advanced and recurrent colorectal cancers. Thus, increasing the treatment efficacy of chemotherapy in colorectal cancer is a must. In this study, doxorubicin (DOX) loaded tumor-targeting peptide-decorated mPEG-P(Phe-co-Cys) nanoparticles were developed to treat orthotopic colon cancer in mice. The peptide VATANST (STP) can specifically bind with vimentin highly expressed on the surface of colon cancer cells, thus achieving the tumor-targeting effects. The nanoparticles are core-shell structured which can protect the loaded DOX while passing through the blood flow and increase the circulation time. The disulfide bonds within the nanoparticles are sensitive to the glutathione-rich microenvironment of tumor tissues. Rupture of disulfide bonds of the nanoparticles leads to the continuous release of DOX, thus resulting in the apoptosis of the tumor cells. The in vivo experiments in mice with orthotopic colon cancer demonstrated that the synthesized DOX loaded tumor-targeting peptide-decorated polypeptide nanoparticles showed properties of drug delivery systems and exhibited good antitumor properties. The synthesized nanoparticles show appropriate properties as one of the drug delivery systems and exhibit good antitumor properties after encapsulating DOX.